The impact of anorexigenic peptides in experimental models of Alzheimer's disease pathology - Maletínská, Lenka; Popelová, Andrea; Železná, Blanka; Bencze, Michal; Kuneš, Jaroslav (The Journal of endocrinology, 2019)
Alzheimer's disease (AD) is the most prevalent neurodegenerative disorder in the elderly population. Numerous epidemiological and experimental studies have demonstrated that patients who suffer from obesity or type 2 diabetes mellitus have a higher risk of cognitive dysfunction and AD. Several recent studies demonstrated that food intake-lowering (anorexigenic) peptides have the potential to improve metabolic disorders and that they may also potentially be useful in the treatment of neurodegenerative diseases. In this review, the neuroprotective effects of anorexigenic peptides of both peripheral and central origins are discussed. Moreover, the role of leptin as a key modulator of energy homeostasis is discussed in relation to its interaction with anorexigenic peptides and their analogs in AD-like pathology. Although there is no perfect experimental model of human AD pathology, animal studies have already proven that anorexigenic peptides exhibit neuroprotective properties. This phenomenon is extremely important for the potential development of new drugs in view of the aging of the human population and of the significantly increasing incidence of AD.
Keywords: Oligopeptides; Animals; homeostáza; Pyrrolidonecarboxylic Acid; kyselina pyrrolidonkarboxylová; Leptin; energetický metabolismus; anorektika; lidé; oligopeptidy; Homeostasis; Energy Metabolism; anorexigenic neuropeptides; leptin; Appetite Depressants; experimental rodent models; modely nemocí na zvířatech; Neuroprotective Agents; Alzheimer Disease; Alzheimer’s disease pathology; Disease Models, Animal; Alzheimerova nemoc; zvířata; neuroprotektivní látky; Humans